0
$\begingroup$

Let $(X,A), (Y,B)$ be measurable spaces. $\mu$ is a measure on $A$, and $h:X\to Y$ a measurable function. Define $\eta: B\to [0,\infty]$ such as $\forall E\in B$ , $\eta(E)= \mu(h^{-1}(E))$.

A. Show that $\eta$ is well defined and is a measure on $B$.

B.Prove: $\forall E\in B \int_{Y} \chi_E d\eta= \int_X (\chi_E\circ h) d\mu$.

C.Let $\phi : Y\to [0,\infty)$ be a simple measurable function. Prove $\int_{Y} \phi d\eta= \int_X (\phi\circ h) d\mu$.

D.Let $f:Y\to\ [0,\infty]$ be a measurable function. Prove $\int_{Y}f d\eta= int_X (f\circ h) d\mu$.

My solution:

A.$\eta(\emptyset)=\mu(h^{-1}(\emptyset))$ then I did not manage to show that it is exactly $\mu(\emptyset)=0$. Let $E_1,E_2,\ldots \in B$ nonoverlapping sets so $\eta(\cup_{i=1}^{\infty}(E_i))=\mu(h^-1(\cup_{i=1}^{\infty}(E_i)))=\mu(\cup_{i=1}^{\infty} h^-1(E_i))= \sum_i \mu(h^-1(E_i))=\sum_i \eta(E_i)$. What does it mean that $\eta$ is well defined?

B.$\forall E\in B, \mu(E)=\int_{E} 1 d\mu=\int_Y \chi_E d\mu$ I did not succeed to finish it!.

C. We can write $\phi=\sum_{j=1}^{n} a_{j} \chi_{E_j}$ where $E_j$ are measurable. Then $\int_Y \phi d\eta= \int_Y \sum_{j=1}^{n} a_{j} \chi_{E_j} d\eta$ = ($\phi_n$ is a sequence of measurable positive functions)= $\sum_{j=1}^{n} a_{j} \int_Y \chi_{E_j} d\eta$ =(by part b) = $\sum_{j=1}^{n} (a_{j} \int_X (\chi_{E_j}\circ h)) d\mu = \int_X (\phi\circ h) d\mu$.

D. f is measurable therefore by a theorem, there is an increasing monotone sequence of simple measurable sets $\phi_n$ such that: $lim_{n\to \infty}\phi_n=f$ and by using the monotone theorem of Lebesgue we get

$\int_Y f d\eta= lim_{n\to \infty} \int _Y \phi_n d\eta$= (by part c)= $lim_{n\to \infty} \int_X (\phi_n\circ h) d\eta$ = ($\phi_n\circ h$ is measurable as a composition of two measurable functions)= $\int_X lim_{n\to \infty} (\phi_n\circ h) d\eta= \int_X (f\circ h ) d\eta$.

I will be glad if you can help in the points which I did not succeed, and tell me if what i did manage was okay.

$\endgroup$
1
$\begingroup$

For part A, that $\eta $ is well defined means that the expression $\eta (E)$ makes sense, and it does because $h^{-1}(E)$ is $\mu$-measurable. By the other side the preimage of the empty set is empty for every function, just note that $$ h^{-1}(A):=\{x:h(x)\in A\} $$ So, when $A=\emptyset $ then $h^{-1}(\emptyset )=\emptyset $.

For the part B note that $$ (\chi _E\circ h)(x)=1\iff h(x)\in E\iff x\in h^{-1}(E)\iff \chi _{h^{-1}(E)}(x)=1 $$

so $\chi _E\circ h=\chi _{h^{-1}(E)}$, and so the relation between the integrals is trivially true in view of the definition of $\eta $.

$\endgroup$
2
  • $\begingroup$ Thanks! Can you please explain how to move to integrals in part b, I understood your approach but did not manage to connect it to integrals. Is what I solved in c and d seems fine? $\endgroup$
    – user726608
    Nov 16 '20 at 16:14
  • 1
    $\begingroup$ @user726608 you already solved part C and D correctly. For the integral of part B this is immediate from my answer above, just note that, by definition $\int \chi _{h^{-1}(E)}\mathop{}\!d \mu =\mu (h^{-1}(E))=\eta (E)$ $\endgroup$
    – Masacroso
    Nov 16 '20 at 17:33

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.